Financial structure, digital transformation, and profitability islamic banks: The role of mediating operational efficiency in southeast asian context - Asbi Amin; Dara Ayu Nianty; Buyung Romadhoni (Institute of Accounting Research and Novation (IARN), 2026)
This research investigates to analyze the influence of financial structure and digital transformation on the profitability of Islamic banks with operational efficiency as a mediation variable. Previous studies have generally examined the determinants of profitability separately, so empirical evidence on the simultaneous role of these two factors through operational efficiency in Islamic banks in Southeast Asia is limited. This study uses a quantitative approach with descriptive and associative design. The sample was determined through purposive sampling of 19 Islamic banks in Southeast Asia during the period 2020–2024, resulting in 95 company year observations. Data analysis was carried out using panel data regression. The results show that financial structure has a negative and significant effect on operational efficiency and profitability, while digital transformation has a positive and significant effect on both. Operational efficiency mediates the effect of financial structure on profitability, but not the effect of digital transformation. Theoretically, this study enriches the literature on Islamic banking profitability by emphasizing the role of operational efficiency as a crucial mechanism linking financial structure and bank performance.